THE DEVELOPMENT OF INTEGRATED LEARNING BASED STUDENTS’ BOOK TO IMPROVE ELEMENTARY SCHOOL STUDENTS’ COMPETENCE - Amini, Risda (Unnes Science Education Journal, 2017)
Integrated learning is planned based on the theme to relate several subjects that able to give meaningful experience to students. Natural science subject is themed to discuss about natural phenomena, which materials was obtained from mindset and observation. Natural science should be introduced from childhood to Elementary School students to make the students able to think critically, creatively, and build scientific characters. Initial survey results showed that elementary school students were difficult in providing students’ thematic learning effectively; thereby, many students were difficult to learn and answer the questions in the online handout. Integrated learning is one of the models which can improve students’ competence. To use this model, students’ book is needed. This research was conducted to develop students’ book based on integrated learning model which were valid, pratical, and effective to accelerate students’ competence. This research and development used Plomp model with three steps: preliminary research, prototyping phase, and assessment phase. The instruments of this research were interview guides, observation sheets, teachers and students’ questionnaires, students’ test result, skills and behavior and skills scoring sheets. The result of this research showed that the developed students’ book has been valid based on experts’ judgement, teachers’ responses and students. The application of students’ book was effective to improve students’ competence.